2018
DOI: 10.3390/geriatrics3010003
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aging: Illness and Social Connections

Abstract: Abstract:The objective of this study was to examine the role of social determinants of health: gender, income, education, housing, and social connections in successful aging in older adults aging with illness. Participants were 50 adults aged 65-90 years, all aging in place in their own home, and reporting at least one illness. This pilot study used non-probability sampling and employed both online and in-person interviews. The majority (82%) were aging "successfully" or "somewhat successfully" as reported on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…Living in a house owned by them might have effects on the results because it is a factor that affects the frequency of changing the environment they live in, namely the probability of living in the environment longer. Different results reported in another study indicated that the majority of individuals aged between 65 and 90 who had a chronic disease accepted that they were ageing successfully and that no relationships were found between the Successful Ageing Scale and gender, income level, education, and place of residence . This result is considered to have been affected by the differences in the way cultural structure and chronic disease processes are managed by the health system.…”
Section: Discussionmentioning
confidence: 80%
“…Living in a house owned by them might have effects on the results because it is a factor that affects the frequency of changing the environment they live in, namely the probability of living in the environment longer. Different results reported in another study indicated that the majority of individuals aged between 65 and 90 who had a chronic disease accepted that they were ageing successfully and that no relationships were found between the Successful Ageing Scale and gender, income level, education, and place of residence . This result is considered to have been affected by the differences in the way cultural structure and chronic disease processes are managed by the health system.…”
Section: Discussionmentioning
confidence: 80%
“…Pretpostavljamo da taj rezultat nije u potpunosti realan i da je možda posljedica izmijenjenih očekivanja starijih osoba u pogledu vlastitog zdravlja, pri čemu starije osobe neke od kroničnih bolesti koje možda i imaju vjerojatno ne smatraju dovoljno ozbiljnima ili ih smatraju normalnima za stariju dob pa o njima ni ne izvješćuju. No, u ovom kontekstu je potrebno razmotriti i suprotne rezultate istraživanja prema kojem većina starijih osoba s oboljenjima za sebe smatra da su uspješno stareće (Carver, Beamsh i Phillips, 2018), što svakako upućuje na potrebu daljnjeg ispitivanja specifične uloge bolesti i zdravlja u kontekstu ovog konstrukta.…”
Section: Raspravaunclassified
“…Population ageing is one of the most important problems of humanity, and the percentage and absolute increase of the elderly population is one of the essential characteristics of the contemporary era, and successful ageing is one of the basic psychological needs of the population [2]. This concept includes various factors such as psychological, physical and social health, mobility and satisfaction with quality of life, financial stability, physical activity, spirituality, etc., this attitude is relevant to the population.…”
Section: Introductionmentioning
confidence: 99%